Elevated Plasma Levels of Matrix Metalloproteinase-3 and Tissue-Inhibitor of Matrix Metalloproteinases-1 Associate With Organ Dysfunction and Mortality in Sepsis. Issue 1 (January 2022) - Jones, Tiffanie K.; Reilly, John P.; Anderson, Brian J.; Miano, Todd A.; Dunn, Thomas G.; Weisman, Ariel R.; Agyekum, Roseline; Feng, Rui; Ittner, Caroline A.G.; Shashaty, Michael G.S.; Meyer, Nuala J.
ABSTRACT: Background: Matrix Metalloproteinases (MMP) respond to tissue damage during sepsis. Higher plasma concentrations of MMPs and the tissue-inhibitor of matrix metalloproteinases (TIMP) have been reported in sepsis compared with healthy controls. The objective of this study was to examine if plasma levels of MMP-3, MMP-9, and TIMP-1 associate with mortality and organ dysfunction during sepsis. Methods: We conducted a prospective cohort study of critically ill patients with sepsis adjudicated per Sepsis-3 criteria at a tertiary academic medical center. We measured plasma concentrations of MMP-3, MMP-9, and TIMP-1 on intensive care unit admission. We phenotyped the subjects for shock, acute respiratory distress syndrome (ARDS), acute kidney injury (AKI), and mortality at 30 days. We used logistic regression to test the associations between the MMPs and TIMP-1 with shock, ARDS, AKI, and mortality. Results: Higher plasma TIMP-1 levels were associated with shock (odds ratio [OR] 1.51 per log increase [95% CI 1.25, 1.83]), ARDS (OR 1.24 [95% CI 1.05, 1.46]), AKI (OR 1.18 [95% CI 1.01, 1.38]), and mortality (OR 1.20 [95% CI 1.05, 1.46]. Higher plasma MMP-3 concentrations were associated with shock (OR 1.40 [95% CI 1.12, 1.75]) and mortality (OR 1.24 [95% CI 1.03, 1.48]) whereas MMP-9 levels were not associated with outcomes. Higher plasma TIMP-1 to MMP-3 ratios were associated with shock (OR 1.41 [95% CI 1.15, 1.72], P = 0.02). Conclusion: Elevated plasma concentrations of TIMP-1 associate with organ dysfunction and mortality in sepsis. Higher plasma levels of MMP-3 associate with shock and mortality. Plasma MMP and TIMP-1 may warrant further investigation as emerging sepsis theragnostic biomarkers. Abstract : Supplemental Digital Content is available in the text